Structural and construct validity of the Czech version of the Pittsburgh Sleep Quality Index in chronic insomnia - Dudysová, Daniela; Malá, Ivana; Mladá, Karolína; Saifutdinova, Elizaveta; Koprivova, Jana; Sos, Peter (Neuro endocrinology letters, 2017)
OBJECTIVES: The Pittsburgh Sleep Quality Index (PSQI) is one of the widely used and recommended measures of assessing sleep quality in chronic insomnia; however certain psychometric properties of the questionnaire are still unknown in this group of patients. The present study aimed to examine the internal consistency, and structural and convergent validity of the Czech version of the PSQI in chronic insomnia patients. The usefulness of the standard and alternative scoring systems was also investigated in relation to symptoms of sleepiness, insomnia, depression, and anxiety. METHODS: In our study, 105 participants filled out a series of questionnaires including PSQI, Insomnia Severity Index (ISI), Epworth Sleepiness Scale (ESS), and Beck Depression and Anxiety Inventories (BDI, BAI). RESULTS: The internal consistency of the questionnaire using Cronbach's alpha was 0.608. A series of confirmatory factor analyses revealed adequate fit for three structures. A three-factor model descriptively stood out among the rest but subsequent correlational analyses did not provide sufficient support for accepting an alternative scoring model. CONCLUSIONS: The results highlight the issue of structural variance of the PSQI and in chronic insomnia point to the important role of the PSQI components of daytime dysfunction and sleep disturbances in showing comorbid symptoms with daytime sleepiness and psychopathology.
Keywords: Male; Factor Analysis, Statistical; lidé středního věku; senioři nad 80 let; Sleep Initiation and Maintenance Disorders; stupeň závažnosti nemoci; Aged, 80 and over; Surveys and Questionnaires; spánek; Humans; chronická nemoc; Reproducibility of Results; Middle Aged; Sleep; senioři; úzkost; reprodukovatelnost výsledků; Česká republika; mužské pohlaví; Czech Republic; Female; mladiství; Anxiety; Aged; deprese; psychometrie; Polysomnography; Psychometrics; ženské pohlaví; průzkumy a dotazníky; Severity of Illness Index; mladý dospělý; Adult; Chronic Disease; Young Adult; polysomnografie; poruchy iniciace a udržování spánku; Depression; Adolescent; dospělí; lidé; faktorová analýza statistická